Irradiation effect on leaf sclerophylly, gas exchange and stomata in sweet orange (Citrus sinensis) - KULDEEP SINGH; O P AWASTHI; AWTAR SINGH; REENA PRUSTY; PRACHI YADAV (The Indian Journal of Agricultural Sciences, 2022)
The study was carried out in mutated population of sweet orange [Citrus sinensis (L.) Osbeck] cv. Mosambi developed from varying dose of gamma rays (10-35 Gy) to determine its effect on leaf sclerophylly, photosynthesis and leaf anatomical characters at the Division of Fruits and Horticultural Technology, ICAR-Indian Agricultural Research Institute, New Delhi during 2017 and 2018. As compared to wild type leaf area, fresh and dry mass was stimulated by 19.53, 18.42 and 20.37% in mutant GS-3 developed from 10 Gy, while in the mutants GS-33 and GS-35 developed from 35 Gy >50% inhibitory effects were noticed. Leaves were however, 82.06% more succulent in the mutant developed from 30 Gy. Mutated population showed dose dependent effect with regard to SLA, SLW and DFT. A significant decline in the photosynthetic rate and stomatal conductance was noticed at 35 Gy in GS-32, whereas mutant GS-34 developed from the same irradiation dose had the minimum transpiration rate. Stomata length and width in the mutants GS-17 and GS-15 as compared to wild type registered an increase of 25.50% and 15.96%. A general reduction in stomata number was observed in the mutated populations. Our result indicated alteration in traits of the mutated population which are of significance and can be used as a selection criterion for improvement of sweet orange.